Why we heal: The evolution of psychological healing and implications for global mental health. (December 2020) - Kohrt, Brandon A.; Ottman, Katherine; Panter-Brick, Catherine; Konner, Melvin; Patel, Vikram
Abstract: Why do humans heal one another? Evolutionary psychology has advanced our understanding of why humans suffer psychological distress and mental illness. However, to date, the evolutionary origins of what drives humans to alleviate the suffering of others has received limited attention. Therefore, we draw upon evolutionary theory to assess why humans psychologically support one another, focusing on the interpersonal regulation of emotions that shapes how humans heal and console one another when in psychosocial distress. To understand why we engage in psychological healing, we review the evolution of cooperation among social species and the roles of emotional contagion, empathy, and self-regulation. We discuss key aspects of human biocultural evolution that have contributed to healing behaviors: symbolic logic including language, complex social networks, and the long period of childhood that necessitates identifying and responding to others in distress. However, both biological and cultural evolution also have led to social context when empathy and consoling are impeded. Ultimately, by understanding the evolutionary processes shaping why humans psychologically do or do not heal one another, we can improve our current approaches in global mental health and uncover new opportunities to improve the treatment of mental illness across cultures and context around the world. Graphical abstract: Unlabelled Image Highlights: Understanding biocultural evolution of psychosocial healing helps improve current practice. Psychological healing is a component of cooperative processes related to evolutionary fitness. Social rupture and social repair are features of cooperative social species including humans. Healing comprises empathy, mirroring, emotional contagion, self-regulation, and mentalizing. Healing among humans involves symbolic processes requiring shared meanings of symbols.